Pengaruh Pemberian Tepung Limbah Kubis Terfermentasi Terhadap Konsumsi Ransum, Konsumsi Protein, Pertambahan Bobot Badan dan Konversi Ransum Ternak Babi Fase Starter - Manibak, Maskrim Letlang; Nalley, Wilmientje Marlene; Dodu, Tagu (Yayasan Sumber Daya Manusia Cerdas, 2024)
The aim of this research is to increase the source of animal protein from pork, requiring continuous availability of animal feed, providing opportunities for utilizing market vegetable waste. There is a large amount of this waste every day and much of it has not been utilized and even tends to cause environmental pollution. This research used an experimental method, with a randomized block design consisting of 4 treatments with 3 replications so that there were 12 experimental units. Treatment consisted of R0: Basal ration without the use of fermented cabbage waste flour (FCWF) R1: 95% RB + 5% FCWF, R2: 90% RB + 10% FCWC, R3: 85% RB + 15% FCWF. The parameters measured were ration and crude protein consumption, body weight gain and ration conversion. The results of the analysis showed that the treatment had no significant effect (P>0.05) on ration consumption, protein consumption, body weight gain and ration conversion. Based on the results of this research, it was concluded that the level of adding cabbage flour with a percentage of 5%, 10%, 15% gave a relatively similar response.